Tungsten: an essential element in our everyday life - Sánchez-Benítez, Javier (2019)
Tungsten has become an indispensable element for our daily life. Due to its physical and chemical properties, this metal, as well as its alloys, is considered nowadays as a strategic and necessary element, with which we share our life.